The secret horses of Briar Hill - Shepherd, Megan (Yearling, 2018)
In the mirrors of Briar Hill hospital there live winged horses that only Emmaline can see. They are her secret. When Emmaline meets Foxfire, a wounded winged horse hiding in the hospital's garden, she becomes its protector, helping Foxfire fight the Black Horse who hunts by colorless moonlight.